Foldable and portable solar module based energy generation system to meet communication sector power demand in military remote camps - Atef, Ahnaf; Omar Alif, Kazi Mohammed; Ahmed, Jubaer; Bin Haroon Rupak, Md. Tasnim (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.